Dynamic stability analysis of laminated composite plates with piezoelectric layers - Chung, Nguyen Thai; Luong, Hoang Xuan; Xuan, Nguyen Thi Thanh (Vietnam Journal of Mechanics, 2014)
Research on the stability to determine the critical value of structures is a complex issue but of real significance. Piezoelectric composite plate is one of the structures which have the ability to control the mechanical behaviors under loads. One of the prominent capabilities of this structure is the ability to control its vibration and stability. Using the finite element method (FEM) and construction calculation program in Matlab, the authors analyzed the elastic stability of piezoelectric composite plates under dynamic in-plane loads, taking into account damping properties of the structure. Critical loads and other factors affecting the stability of the plate are investigated.